2023
DOI: 10.3390/foods12030643
|View full text |Cite
|
Sign up to set email alerts
|

UHPLC-MS Phenolic Fingerprinting, Aorta Endothelium Relaxation Effect, Antioxidant, and Enzyme Inhibition Activities of Azara dentata Ruiz & Pav Berries

Abstract: Azara dentata Ruiz & Pav. is a small Chilean native plant from Patagonia, a producer of small white reddish berries. For the first time, the proximal analysis of the fruits, phenolic fingerprinting, the antioxidant activity, and the enzymatic inhibition and relaxation effects in rat aorta induced by the ethanolic extract of these fruits were investigated. The proximal composition and the mineral (Ca: 2434 ± 40 mg/kg; Mg: 702 ± 13 mg/kg; Fe: 117.1 ± 1.6 mg/kg; Zn: 16.1 ± 0.4 mg/kg) and heavy metal (As: 121 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 62 publications
(73 reference statements)
1
4
0
Order By: Relevance
“…These results are in agreement with the ORAC assay (Table 2). Our results are in agreement with those from antioxidant plants, but lower in relation to fruits [15,16]. As you can see in Table 2, the TPC of NCM (ethyl lactate/MAE) is almost twice as low as the TPC of CM (MeOH/maceration), while the TFC of NCM is 2.5 times lower than that of CM.…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…These results are in agreement with the ORAC assay (Table 2). Our results are in agreement with those from antioxidant plants, but lower in relation to fruits [15,16]. As you can see in Table 2, the TPC of NCM (ethyl lactate/MAE) is almost twice as low as the TPC of CM (MeOH/maceration), while the TFC of NCM is 2.5 times lower than that of CM.…”
Section: Antioxidant Activitysupporting
confidence: 91%
“…It is mandatory to check the full content of metals in foods. The results of a proximal composition showed that canelo fruits are rich in carbohydrates (58%) and have a high protein content (13%), and the mineral content showed that the fruits are rich in magnesium (77 mg/kg) and potassium (530 mg/kg) but lower in sodium, which make this spice very good for the elderly and better than other fruits such as kiwis or local azaras [ 7 ]. Black pepper showed 2636.97 mg/kg Ca, 10,006.04 mg/kg K, and 1486.94 mg/kg mg; however, it also showed 1892.12 mg/kg Na [ 31 ], while the famous spice Capsicum annuum showed 1160.04 mg/kg Ca, 1253.65 mg/kg mg, and 16,143.58 mg/kg Na [ 31 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, our group reported the inhibition of AChE, BChE, and tyrosinase for several endemic and native species from Chile. For example, endemic A. dentata’s berry ethanolic extract showed an IC 50 of 2.87 ± 0.23 µg/mL, 6.73 ± 0.07 µg/mL, and 9.25 ± 0.15 µg/mL against AChE, BChE, and tyrosinase, respectively [ 7 ], while the n-hexane extract of the endemic G. pinifolium plant showed an IC 50 of 4.58 ± 0.04 µg/mL, 23.44 ± 0.03 µg/mL, and 9.25 ± 0.15 µg/mL against AChE, BChE, and tyrosinase, respectively. G. pinifolium ethyl acetate extract showed AChE (IC 50 6.43 ± 0.03 µg/mL), BChE (IC 50 33.25 ± 0.02 µg/mL), and tyrosinase (IC 50 12.32 ± 0.21 µg/mL) [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations